2001
DOI: 10.1074/jbc.m010626200
|View full text |Cite
|
Sign up to set email alerts
|

ENaC Degradation in A6 Cells by the Ubiquitin-Proteosome Proteolytic Pathway

Abstract: Amiloride-sensitive epithelial Na؉ channels (ENaC) are responsible for trans-epithelial Na

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
100
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(109 citation statements)
references
References 26 publications
(35 reference statements)
8
100
1
Order By: Relevance
“…However, in epithelial cells, ␤-ENaC appears to act as an auxiliary subunit to regulate ENaC activity and trafficking to the plasma membrane (20 -22). Although the data from other investigators have shown that aldosterone has no chronic effect on the expression of ␤-ENaC in rat kidney (22,23), our results have shown that aldosterone stimulates expression of ␤-ENaC in A6 cells (24). Therefore, it is possible that the ␣-ENaC channel in human B lymphocytes is regulated by aldosterone via expression of the ␤ subunit.…”
Section: Resultscontrasting
confidence: 82%
See 2 more Smart Citations
“…However, in epithelial cells, ␤-ENaC appears to act as an auxiliary subunit to regulate ENaC activity and trafficking to the plasma membrane (20 -22). Although the data from other investigators have shown that aldosterone has no chronic effect on the expression of ␤-ENaC in rat kidney (22,23), our results have shown that aldosterone stimulates expression of ␤-ENaC in A6 cells (24). Therefore, it is possible that the ␣-ENaC channel in human B lymphocytes is regulated by aldosterone via expression of the ␤ subunit.…”
Section: Resultscontrasting
confidence: 82%
“…Another steroid, dexamethasone, is known to increase expression of ␤-and ␥-ENaC protein levels in lung epithelial cells (32). Our earlier studies also suggest that aldosterone increases the mRNA level of ␤-ENaC and the protein level of ␥-ENaC in A6 distal nephron cells (24). The concentration of aldosterone we used was high enough that it could have activated both mineralocorticoid and glucocorticoid receptors.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Cleaved Forms of ENaC Are Found on the Cell SurfaceProteolytic processing of ENaC subunits is not restricted to degradation in lysosomes or by proteasomes (19,37), as processed subunits are clearly expressed at the plasma membrane. Jovov et al (38) previously identified trypsin-sensitive sites within the cytoplasmic carboxyl termini of the ␤-and ␥-subunits.…”
Section: N-glycans Are Processed On All Three Subunits Of Enac-mentioning
confidence: 99%
“…KIAA1203 UniGene Cluster Hs.16953 is expressed in kidney and contains ubiquitin carboxyl-terminal hydrolase family two domain which may function, through proteosomal pathway, as a regulator of the amiloride-sensitive epithelial Na(+) channel SCNN1, 44 whose two subunits, SCNN1B and SCNN1G are located in KIAA1203 in close proximity on 16p11.2. Three single base pair substitutions were found in the KIAA1203 gene.…”
Section: Haplotype Analysismentioning
confidence: 99%